2022
DOI: 10.1038/s41467-022-28606-z
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia pools in zeolites for direct fabrication of catalytic centers

Abstract: Reduction process is a key step to fabricate metal-zeolite catalysts in catalytic synthesis. However, because of the strong interaction force, metal oxides in zeolites are very difficult to be reduced. Existing reduction technologies are always energy-intensive, and inevitably cause the agglomeration of metallic particles in metal-zeolite catalysts or destroy zeolite structure in severe cases. Herein, we disclose that zeolites after ion exchange of ammonium have an interesting and unexpected self-reducing feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…Tsubaki and co-workers demonstrated that the ammonium-exchanged zeolites have a self-reducing feature, which can accurately control the reduction of metal–zeolite catalysts and the crystal size of the metals through in situ ammonia production from “ammonia pools”. 71 The ammonia pool effect is not influenced by the topological structures of the zeolites, and works well on reducible metals (Fig. 8b).…”
Section: Recent Methods To Stabilize Supported Metal Catalystsmentioning
confidence: 84%
“…Tsubaki and co-workers demonstrated that the ammonium-exchanged zeolites have a self-reducing feature, which can accurately control the reduction of metal–zeolite catalysts and the crystal size of the metals through in situ ammonia production from “ammonia pools”. 71 The ammonia pool effect is not influenced by the topological structures of the zeolites, and works well on reducible metals (Fig. 8b).…”
Section: Recent Methods To Stabilize Supported Metal Catalystsmentioning
confidence: 84%
“…33 The ammonia pool effect is then conducive to the formation of metal active sites with high dispersion, high activity, and high stability on zeolite catalysts. 34 Secondly, through transient kinetic experiments, we rationally infer that after loading metal species on the parent zeolite, the remaining B acid can also store NH 3 and function as an ammonia pool. 9,20 This part of the ammonia pool not only inhibits the formation of CO 2 but also promotes the effect of the neighboring Sn-L acid on ethane dehydrogenation.…”
Section: Catalyst Evaluationmentioning
confidence: 90%
“…Ion exchange zeolites are widely used for CO 2 hydrogenation, with surface acid sites being regulated by replacing H + from the bridging Al(OH)Si (Brønsted acid sites) with various metal species. 135,212,213 Moreover, the adding of alkali metals via ion exchange method can promote the formation of aromatics in CO 2 hydrogenation. 201 The introduction of small amount of Zn species into ZSM-5 by ion-exchange favours the formation of aromatics from CO 2 .…”
Section: Ion Exchangementioning
confidence: 99%